THE EFFECT OF NB ELEMENT ADDING ON THE THERMODYNAMIC PARAMETERS, CORROSION AND STRUCTURAL PROPERTIES OF NITIZR ALLOY - ABDULLAH, SHAKHAWAN SALIH (Fırat Üniveristesi, 2023)
Biyomühendislik malzemelerinin korozyona karşı direncinin arttırılması tıbbi uygulamalar için büyük önem taşımaktadır. NiTi bazlı şekil hafızalı alaşımların biyouyumluluğunun arttırılmasının araştırılması, çeşitli disiplinler arasında ilgi çekici bir araştırma alanıdır. Bu özel çalışmada, Ti ve Zr'nin sabit atom yüzdesine sahip Ni40-xTi50Zr10Nbx (x = 1, 2, 3, 4 ve 5 at.%) şekil hatirlamali alaşimlarin termal, yapisal ve korozyon davranislari incelendi. Amaç, Ni oranini azaltip biyouyumlu Nb elementi ekleyerek alaşımın biyouyumluluğunu arttırmak. Araştırma, Diferansiyel Taramalı Kalorimetri (DSC) ölçümleri ile termal fazlar incelendi. SEM-EDX ve XRD araştirmaları ile alaşımların yapısal özellikleri belirlendi. Ayrica, alaşımların SBF sıvısında korozyon davranışları detaylı incelendi. NiTiZr Şekil hatırlamalı alaşımlara Nb katkılanınca, alaşımın donusum sıcaklıklarıve faz donusum entalpileri düştügü belirlendi. Mikro yapıda B2, B19' ve cokelti fazları tespit edildi. SBF sıvısında alınan korozyon olcümlerinde Nb artması ile korozyon direnci arttıgı belirlendi.

Enhancing the resistance to corrosion in bioengineering materials holds significant importance for medical applications. The exploration of augmenting the biocompatibility of NiTi-based shape memory alloys is a compelling area of investigation across various disciplines. In this particular study, Ni40-xTi50Zr10Nbx (x = 1, 2, 3, 4, and 5 at.%) with a consistent atomic percentage of Ti and Zr underwent examination. The objective was to enhance the alloy's biocompatibility by substituting Nb for Ni. The investigation included an analysis of the martensitic phase transformation using Differential Scanning Calorimetry (DSC) measurements. The introduction of Nb as an additive exhibited an adverse effect on the martensitic phase transformation, potentially causing a shift in composition within the phase diagram. Tafel testing and electrochemical impedance spectroscopy conducted in a simulated body fluid (SBF) demonstrated that the incorporation of Nb improved the corrosion resistance of the alloy. This improvement was attributed to an increase in the thickness of the protective oxide layer at the interface between the alloy and electrolyte. By replacing an optimal proportion of Ni with Nb, the biocompatibility of the NiTiZr-based alloy was enhanced while preserving its shape memory characteristics.
Nb element ilavesinin NiTiZr alaşımının termodinamik parametreleri, korozyon ve yapısal özellikleri üzerine etkisi
Keywords: Fizik ve Fizik Mühendisliği